A systematic review of urban agriculture and food security impacts in low-income countries. (August 2015) - Poulsen, Melissa N.; McNab, Philip R.; Clayton, Megan L.; Neff, Roni A.
Highlights: We review data on urban agriculture and food security in low-income countries. Producing food for household consumption drives participation in urban agriculture. Urban agriculture can positively impact food availability and dietary diversity. It may provide household income, but not always enough to ensure food security. Urban agriculture can create distinct benefits for women, financially and socially. Abstract: With increasing global urbanization and environmental threats, ensuring food security for poor city residents is a critical challenge. An ongoing debate is whether urban agriculture (UA) may serve as a pathway to food security for poor urban households. To assess this potential within low-income countries, we used standard systematic review procedures to synthesize findings from 35 peer-reviewed journal articles from 1980 to 2013 that presented data on UA and food security indicators. Though data quality was often lacking, several key findings emerged. Many of the reviewed studies found subsistence to be the primary motivation for practicing UA, followed by financial benefit, with UA substantially contributing to farming households' food availability in some settings. Results regarding UA's impact on dietary diversity reveal that in some farming systems UA may provide households with greater access to specific foods. Evidence also indicates that UA can be a key source of household income, though actual returns were low. Furthermore, results show that UA can facilitate women's contribution to household food availability amid other household responsibilities, and can provide distinct benefits such as economic and social advancement. Although UA participation does not appear to fully eliminate pressure urban households face in obtaining food, a lack of supportive policies may constrain its potential. Municipal planning and agricultural policies that more effectively incorporate UA—and that integrate gender—may diminish barriers to productive UA practice. More rigorous research on UA's contribution to food security in settings where supportive policies have been enacted would more clearly elucidate these linkages.